Peningkatan Kompetensi Algoritma Pemrograman untuk Guru SMK Negeri 1 Salatiga - Maria, Evi; Winarso Martyas Edi, Sri; Suharyadi; Christianto, Erwien; Purwanto (Warta LPM, 2023)
Accounting teachers at the State Vocational High School (SMK) 1 Salatiga currently have the competence to record manual accounting and accounting applications already available on the market. However, the World of Business and Industry  demands that SMK graduates be able to develop simple accounting applications for Small and Medium Enterprises (SMEs). Application development requires mastery of programming algorithm competencies to help think more logically, creatively, and critically. This condition encourages accounting and computer teachers at SMK Negeri 1 Salatiga to need the training to improve algorithmic and programming competencies. This community service activity aims to enhance the competence of programming algorithms for accounting and computer teachers at SMK Negeri 1 Salatiga. The presentation of the material is arranged by the mentors so that this training program can be completed quickly and the objectives are achieved. There are three methods of implementing the activity: (1) socialization of programming algorithm material; (2) programming algorithm training activities; (3) case practice of programming algorithms. Participants in this activity were ten teachers at SMK Negeri 1 Salatiga, namely nine teachers majoring in accounting and one computer teacher. This activity was held in September 2022. Competency improvement was measured by conducting a pre-test and post-test on activity participants regarding programming algorithm material using a questionnaire containing 30 multiple-choice questions. The result of this activity is an increase in the competency of the participant's programming algorithm from 10 percent to 90 percent, and the activity participant’s can solve cases of programming algorithms and document them using the flowgorithm correctly.